Trends in COVID-Related Activity in Sentinel Family Medicine Practices: An Observational Study - Muriel Maeder; Diane Auderset; Bernard Borel; Eric Masserey; Joëlle Schwarz; Yolanda Mueller (International Journal of Public Health, 2023)
Objectives: During the COVID pandemic, data collected in family medicine were scarce. The COVID-FM project aimed to monitor trends of COVID-related activity in family medicine practices of the canton of Vaud, Switzerland, during the year 2021.Methods: Practitioners were invited to join an ad hoc sentinel surveillance system. Online data collection was based on daily activity reports and monthly questionnaires. Participants categorized daily counts of consultations and phone calls into predefined categories. Data were reported and discussed on a weekly basis with public health authorities.Results: On the target of 50 physicians, 37 general physicians from 32 practices finally constituted the COVID-FM sentinel network, contributing to 901 practice-weeks of surveillance in family medicine and 604 in paediatrics. In paediatrics, COVID-related activity corresponded mostly to COVID-19 diagnostic consultations (2911/25990 face-to-face consultations = 11.2%) while in family medicine, other COVID-related topics—such as questions on vaccination—predominated (4143/42221 = 9.8%).Conclusion: COVID-related consultations constituted an important part of primary care practices’ activity in 2021. Monitoring COVID-related activity in primary care provided health authorities with valuable information to guide public health action.